Modeling the economywide effects of water and energy interventions in the face of climate change - Aragie, Emerta A.; Gebretsadik, Yohannes (International Food Policy Research Institute, 2023)
The Ethiopian economy relies predominantly on rainfed agriculture for income generation, export earnings, and rural livelihoods. However, the frequency and intensity of extreme ago-climatic events projected by climate scenarios suggest considerable and growing risks from climate change to the country’s agri-food systems and the overall economy. This study assesses the economic impacts of recurrent climate shocks on the Ethiopian economy to 2040. The results indicate that recurrent climate shocks will lead to a reduction in Ethiopia's cumulative GDP from 2020 to 2040 compared to a “no climate change” baseline. Specifically, extreme weather events could cumulatively cost Ethiopia up to 17 percent (or US$ 534.3 billion) in GDP between 2020 and 2040 compared to a no-climate change baseline. The weight of the economic loss is concentrated in the agricultural production sector, with rural households and poorer households in urban areas being worst affected. Strategic investments in irrigation infrastructure and in hydroelectricity generation are found to be effective in mitigating some of the damage caused by recurrent climate variability.